Transparent and Flexible Photo‐Driven Smart Window Display Displayed by Near‐Infrared Laser. Issue 34 (13th October 2022) - Yang, Jonguk; Lim, Taekyung; Ju, Sanghyun
Abstract: A smart window is an active light control technology that can freely control the transmittance of light, thereby improving the energy efficiency of the interior space and providing a comfortable environment through the control of sunlight from the outside. In this study, a novel smart window that can be utilized as an information‐providing display is developed by a simple light‐blocking technology for existing smart windows. A transparent flexible smart window board is fabricated by inserting a hydroxypropyl cellulose (HPC)–cesium tungsten oxide (CTO) composite hydrogel between two transparent substrates. When the smart window board is irradiated with a near‐infrared (NIR) laser, the heat emitted from the CTO absorbing the NIR energy is transferred to the HPC, thereby changing the visible light transmittance of the HPC. Because only the portion irradiated with the NIR laser can selectively change the visible‐light transmittance, various types of images can be formed in real time. The proposed photo‐driven smart window display can be utilized as a novel platform for window displays that can express various images in real time and can act as a curtain by adjusting the transmittance of light, changing to transparent/opaque, which is oriented in existing smart windows. Abstract : A transparent and flexible smart window board is fabricated by inserting a hydroxypropyl cellulose–cesium tungsten oxide composite hydrogel. When the near‐infrared (NIR) laser is irradiated to the composite hydrogel, it appears visually white due to the strong interaction between CH. The desired image and video can be realized by controlling the transparent/opaque state according to the NIR laser irradiation.